Macrophage is crucial for tongue development by regulating myogenesis and vascularization - Ziyao Wang; Mengqiao Wang; Jiani Liu; Delu Zhao; Jixiao Wang; Fulan Wei (BMC Oral Health)
Abstract Background Abnormal tongue development is a craniofacial deformity that affects dental-maxillofacial esthetics and function. Recent evidence has identified macrophages as multi-functional immune cells crucial for heart and brain development. However, it is still unknown whether macrophages affect tongue development. Therefore, this study aims to assess the distribution, phenotype, and roles of macrophages in the developing tongue. Methods In this study, immunohistochemical (IHC) and multiplex immunofluorescence (mIF) staining were conducted on C57BL/6 mice at embryonic day (E) 13.5, E14.5, E16.5, and E18.5 to analyze the distribution and phenotype of macrophages. Hematoxylin–Eosin (HE), IHC, IF, and mIF staining were also performed on embryonic CX3 CR1-CreERT2; Rosa-DTA conditional macrophage-depleted mice to investigate the effects on fetal tongue development and elucidate mechanisms from myogenesis, vascularization, and cell apoptosis. Statistical significance between the two groups was determined using unpaired two-tailed Student’s t-tests. For comparisons involving three or more groups, one-way analysis of variance (ANOVA) followed by Tukey’s multiple comparison tests was utilized. A significance level of P < 0.05 was set for statistical significance. Results Macrophages were present in the developing tongue from E13.5 to E18.5, with a majority being of the M2 phenotype. Depletion of macrophages resulted in abnormal tongue morphology, decreased tongue height, width, and size, as well as reduced and disorganized muscle fibers. Depletion of macrophages also increased apoptosis. Vascular morphogenesis was impacted, with reductions in the luminal and vascular wall cross-sectional areas of the lingual artery. Vascular endothelial cells were reduced and disorganized with decreased expression of VEGFA and TGF-β1. Moreover, macrophages were located near vascular endothelial cells and secreted pro-angiogenic factors, suggesting their involvement in promoting vascularization. Conclusions Our findings indicate that macrophages play crucial roles in fetal tongue development by affecting myogenesis, cell apoptosis, and vascular growth.